Characteristics of nonverbal communication interaction between doctor and patient - Milićević, Milena (PONS - medicinski časopis, 2018)
Objective. In the health sector, over the past decades, great importance is given to good interpersonal and communication skills as one of the key characteristics of health care workers. Numerous studies of empirical character have followed the impact that interpersonal communication has on the behavior of a patient, on the treatment outcomes and patient satisfaction with the service. The aim of this study was to present the health communication through a brief review of studies focused on non-verbal communication in the interaction between doctor, as a health care worker and patient, as a user of health services is provided. Method. On the basis of the available literature, an overview of research focused on nonverbal communication in the interaction between a physician and a patient. Characteristics of nonverbal behavior in the interaction, as a professional contact between a physician and a patient, were analyzed from the aspect of health communication. Results. The results have confirmed that the interpersonal communication between doctor and patient is complex, dynamic and under the multiple influences of a whole range of different factors. Doctor’s non-verbal communication skills are associated with many positive outcome results, such as both patient and physician satisfaction, higher rates of adherence to therapeutic recommendations, improved physiological parameters and control of the disease, improvement of physical and mental health and functional status. Conclusion. Understanding interpersonal communication within the doctor-patient dyad creates a good basis for improving the effectiveness and raising the quality of health services.